Better rooting procedure to enhance survival rate of field grown Malaysian eksotika papaya transformed with 1-aminocyclopropane-1-carboxylic acid oxidase gene - Sekeli, Rogayah; Abdullah, Janna Ong; Namasivayam, Parameswari; Muda, Pauziah; Abu Bakar, Umi Kalsom (Hindawi Publishing Corporation, 2013)
A high survival rate for transformed papaya plants when transferred to the field is useful in the quest for improving the commercial quality traits. We report in this paper an improved rooting method for the production of transformed Malaysian Eksotika papaya with high survival rate when transferred to the field. Shoots were regenerated from embryogenic calli transformed with antisense and RNAi constructs of 1-aminocyclopropane-1-carboxylic acid oxidase (ACO) genes using the Agrobacterium tumefaciens-mediated transformation method. Regenerated transformed shoots, each measuring approximately 3-4 cm in height, were cultured in liquid half-strength Murashige and Skoog (MS) medium or sterile distilled water, and with either perlite or vermiculite supplementation. All the culturing processes were conducted either under sterile or nonsterile condition. The results showed that rooting under sterile condition was better. Shoots cultured in half-strength MS medium supplemented with vermiculite exhibited a 92.5% rooting efficiency while perlite showed 77.5%. The survival rate of the vermiculite-grown transformed papaya plantlets after transfer into soil, contained in polybags, was 94%, and the rate after transfer into the ground was 92%. Morpho-histological analyses revealed that the tap roots were more compact, which might have contributed to the high survival rates of the plantlets.